Maskulinitas tokoh utama d’Artagnan dalam novel Les Trois Mousquetaires karya Alexandre Dumas - Concita, Jordy; Andika, Yunilis; Ismail, Subur (Franconesia, 2023)
This study aims to analyzing the masculinity of D’artagnan in the novel Les Trois Mousquetaires by Alexandre Dumas, by using seven characteristics of masculinity according to Chafetz (1974) which are Physical, Functional, Sexual, Emotional, Intellectual, Interpersonal and Other personal. This research method is a qualitative descriptive analysis using a structural approach to literary works. The first stage of analysis is to describe the intrinsic elements of the novel which are plot, characterisation and setting. The next stage is to identify and interpret the data findings in the form of words, phrases, sentences and contexts in the data source that indicate the existence of masculinity characteristics. The results of this study show that there are thirty-two (32) data that indicate the characteristics of masculinity. In detail, of the thirty-two (32) quotations, eight (8) quotations of Other personal characteristics, seven (7) quotations of Emotional characteristics, six (6) quotations of Intellectual characteristics, six (6) quotations of Interpersonal characteristics, two (2) quotations of Physical characteristics, two (2) quotations of Sexual characteristics and one (1) quotation of Functional characteristics.